The grammar of temporal motion: A Cognitive Grammar account of motion metaphors of time - Huumo Tuomas (De Gruyter Mouton, 2022)
Abstract: Recent groundbreaking work in cognitive linguistics has revealed the
semantic complexity of motion metaphors of time and of temporal frames of
reference. In most approaches the focus has been on the clause-level metaphorical
meaning of expressions, such as MOVING EGO (We are approaching the end
of the year) and MOVING TIME (both EGO-CENTERED, as in The end of the year is
approaching and FIELD-BASED, as in Boxing Day follows Christmas Day). The
detailed grammatical structure of these metaphorical expressions, on the other
hand, has received less attention. Such details include both elements that
contribute to the metaphorical meaning and those that have a non-metaphorical
temporal function, e. g., tense and (central features of) aspect. I propose a model
for the analysis of metaphorical expressions, building on earlier work in
Conceptual Metaphor Theory and the framework of Cognitive Grammar (CG).
I approach the grammatical structure of metaphorical expressions by analyzing
the interplay between veridical and metaphorical systems of expressing temporal
relations. I argue that these systems relate to two relevant conceptualizations
of time. Veridical time (VT) is the non-metaphorical conceptualization of
time, where the processual profile of the clause-level metaphorical expression
resides. A metaphorical path (MP) is the metaphorical conceptualization of time
as a path occupied by the metaphorical motion. A motion metaphor of time
tracks the MOVER’s changing position on the MP against VT. I show how
metaphorical expressions based on a motion verb differ from those based on a
prepositional construction in grammatical and semantic terms, and how tense
and aspect contribute to the conceptualization of the motion scenario. I argue
that tense grounds the metaphorical motion event with respect to the speech
event. All the participants in the motion event, as well as the metaphorical path
itself, are present in each subsequent configuration tracked against VT by the
conceptualizer. Thus tense has a wide scope over the motion scenario with Ego’s
‘now’ as a reference point, while Ego’s ‘now’ cannot serve for grounding of
tense. This is why expressions such as *The meeting is difficult ahead of us are
not acceptable.